A CROSS-SECTIONAL STUDY ASSESSING THE ASSOCIATION BETWEEN PERIODONTAL DISEASE AND SOCIO-BEHAVIORAL RISK FACTORS - Oana Chipirliu; Marian Viorel Crăciun; Mădălina Nicoleta Matei (Romanian Journal of Oral Rehabilitation)
Aim of the study The objective of this study was to know and evaluate the level of knowledge and skills on oral hygiene in a population group of children with cardiovascular diseases by means of a questionnaire and thus achieving the classification in a certain class of periodontal risk, in order to design and implement an educational program tailored to the needs and interests of this category of patients. Material and methods The total group of patients included in the study consisted of 124 patients who were divided into four groups: group A-31 patients with cardiovascular disease and periodontal disease, group B-31 patients with cardiovascular disease and without periodontal disease, group C-31 patients without cardiovascular disease but with periodontal disease, group D-31 patients without cardiovascular disease and without periodontal disease. A clinical and observational survey study was conducted using a questionnaire. To assess local hygiene and inflammation status, in this study we used the O’Leary plaque index (PI) and the Silness and Löe gingival index (GI). The questionnaire was designed in four sections and presented pre-selected multiple-choice questions with a square that patients checked for the answer they considered correct. The questionnaire was used to assess oral hygiene knowledge and skills in a population group of children. Results For patients in group A, even if the daily hygiene program is better than for patients in group C, the clinical inflammatory manifestations are more evident, which is demonstrated by the high GI values, showing the influence of the general condition on the local inflammatory status. Secondary means of oral hygiene are rarely used by respondents; 77.4% of respondents in group A and 87.1% of respondents in group C do not use secondary means of hygiene. The use of mouthwash is associated with proper hygiene 32.3% of respondents in group B and 54.8% of respondents in group D. Oral health information is mostly obtained from the family, similar percentage for group A and for group C 45.2% of respondents. Conclusions By analyzing the oral hygiene program, the frequency of dental visits, eating habits and general and oral health, an accurate assessment of periodontal risk can be made from childhood, allowing early preventive interventions. Promoting oral health in families, in schools, through early and comprehensive interventions in the young population, can contribute to the growth and development of future adults with the best possible oral health.